The Frequency of Intraventricular Hemorrhage and its Risk Factors in Premature Neonates in a Hospital’s NICU - basiri, behnaz -; Sabzehei, Mohammad Kazem; Shokouhi Solgi, Maryam; Khanlarzadeh, Elham; Moshiri, Mojdeh (Iranian Journal of Child Neurology, 2021)
Abstract Objective Intraventricular hemorrhage (IVH) is an important cause of mortality and disability in premature neonates. Regarding this, the present study aimed to determine the frequency of IVH and its risk factors in the premature newborns admitted to the Neonatal Intensive Care Unit (NICU)at Fatemieh Hospital in Hamedan, Iran, 2016. Materials & Methods This cross-sectional study was conducted on178 neonates with a gestational age of ≤ 32 weeks admitted to Fatemieh Hospital affiliated to Hamadan University of Medical Sciences, Hamedan, Iran, in 2016. The study population was selected using census method. The newborns were subjected to cranial ultrasound on the seventh day of life. and they were assigned into two case and control groups (namely neonates with IVH and those without IVH, respectively). Intra- ventricular hemorrhage was classified into four grades regarding Papile classification. The patients’ demographic specifications, including 1- and 5-minute Apgar scores, type of delivery, birth weight, use of mechanical ventilation, prenatal corticosteroid, gestational age, and some complications (e.g., Pneumothorax), were collected using a checklist. The data were analyzed using SPSS software version 16 Results According to the results, prevalence of IVH in premature infants admitted to NICU was approximately 20 %, , 61.2% of the neonates were male. The mean gestational age of the participants was 30.39 weeks. The comparison of delivery type between the case and control groups showed no significant difference between them in this regard(P=0.197). Furthermore, there was a significant difference between the two groups in terms of need for mechanical ventilation (P=0.03), pneumothorax risk of this condition in the preterm neonates is enhanced by some factors, such as low birth weight, 5-minute Apgar score, and gestational age as well as the need for mechanical ventilation. (P=0.001), and 5-minute Apgar scores (P=0.04). Additionally,the incidence of IVH showed a significant relationship with the mean gestational age (P=0.001) and birth weight (P=0.04). Conclusion According to the findings, the premature newborns admitted to the NICU revealed a relatively high prevalence of IVH. The condition is aggravated in preterm neonates by some factors such as low birth weight, 5-minute Apgar score, gestational age, and the need for mechanical ventilation.